Pengaruh Customer Experience terhadap Repurchase Intention dengan Brand Trust sebagai Mediating Variabel di Monochrome Coffee & Kitchen Kota Padang - Nova Kurnia Julisri Markis; Feri Ferdian; khairani Saladin; Rian Surenda (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2024)
This research is motivated by the discovery of issues related to the low percentage of repurchase intention among customers of Monochrome Coffee & Kitchen in Kota Padang. Complaints about customer dissatisfaction with the products, services, facilities, and the lack of confidence in the 19 Monochrome brand itself have resulted in a reluctance to repurchase products and services at Monochrome Coffee & Kitchen. The aim of this research is to analyze the impact of customer experience on repurchase intention with brand trust as a mediating variable at Monochrome Coffee & Kitchen in Kota Padang. This research is a quantitative type with a causal associative approach, utilizing purposive sampling method, and involving 265 respondents. The data collection method involves distributing questionnaires to respondents based on a Likert scale that has been tested for validity and reliability. Data analysis is conducted using SPSS and SEM (PLS). From this research, it is found that customer experience is categorized as fairly good with a percentage of 59%, repurchase intention is categorized as fairly good with a percentage of 52%, and brand trust is categorized as good with a percentage of 44%. The research results can be observed from the t-statistic and p-values based on SEM (PLS) data analysis, which concludes that customer experience (X) has a significant influence on repurchase intention (Y), customer experience (X) has a significant influence on brand trust (Z), brand trust (Z) has a significant influence on repurchase intention (Y), and customer experience (X) has a significant influence on repurchase intention (Y) through brand trust (Z) as a mediating variable. This implies that all hypotheses in this research are accepted.